Efeito antipsicótico de novos inibidores do transportador de prolina (SLC6A7) - Carvalho, Gustavo Almeida de (2020)
Schizophrenia is a serious psychiatric disorder that expresses a complex set of positive, negative and/or cognitive symptoms. Some hypotheses attempt to explain the cause of schizophrenia, one of which is the glutamatergic hypothesis based on pharmacological evidence and pathophysiological studies that point to a hypofunction of NMDA receptor signaling in the brain. Proline transporters (SLC6A7) are predominantly expressed in the central nervous system (CNS) and are associated with glutamatergic neurotransmission, however, their role in regulating neural function and pharmacological potential is little known. The objective of this work was to pharmacologically characterize new prototypes of proline transporter inhibitors (SLC6A7) and to test the effect of one of these in a ketamine-induced psychosis model. The results presented here demonstrate that the compounds LQFM 215, LQFM 216 and LQFM 217 have a low impact on the viability of LUHMES cells and in culture of peripheral neurons and are capable of reducing the uptake of intracellular proline in synaptosomes. The compound LQFM 215 had a greater impact on the viability of LUHMES cells as well as on peripheral neurons and a greater inhibitory effect on the uptake of proline. In the behavior of mice, the compound LQFM 215 reduced the mobility of the animals, without prejudice to the working memory in the highest tested dose of 10 mg/kg and was not able to induce anxious or depressive behaviors. In the marble burying test the compound LQFM 215 in all the tested doses of 2.5, 5 and 10 mg/kg was able to stimulate this behavior. By testing the compound LQFM 215 in the ketamine-induced psychosis model, he was able to reduce the animals' induced hyperlocomotion at the tested doses of 20 and 30 mg/kg. The set of these results indicates that the compound LQFM 215 is a neuroactive compound with an effect on the mobility of animals and with antipsychotic potential. This work demonstrates that PROT inhibitors can be targets for the development of new antipsychotics.